Respon Pertumbuhan Tomat Ceri Merah Oval (Solanum lycopersicum Var. Cerasiforme) Terhadap Frekuensi Penyiraman yang Berbeda - Ambar Pratiwi; Elisa Sastra; Inggita Utami (Universitas Muhammadiyah Prof. Dr. Hamka, 2021)
Background: Cherry tomatoes are horticultural plant that has high economic value because the fruit has many benefits and uses. Tomato include in Solanaceae family which is susceptible to water shortages. Lack of water in plants usually occurs as a result of drought events. The impact of drought on tomato plants has decreased the growth of tomato plants, their quality and production. This research aims to determine the response of oval red cherry tomato plant growth to different watering frequencies and to determine the watering frequency of oval red cherry tomato plants that show the best growth. Methods: In this research, the provision of different watering frequencies on oval red cherry tomato plants aged 3 weeks for 24 days. The frequency of watering that is given is watering every day, once every 3 days, once every 6 days and 9 days with a volume of 300 mL waters. The parameters observed were the growth of oval red cherry tomatoes including plant height, number of compound leaves, stem diameter, number of flowers and number of fruits, and also ascorbic acid and toal flavonoid content. Results: The results showed that daily watering increased the number of leaves and stem diameter. Meanwhile, watering once every 3 days can increase the height of the oval red cherry tomato plants. Conclusions: The growth responses given to different watering frequencies were the increase in plant height, the number of compound leaves and the stem diameter of the oval red cherry tomatoes.